1997
DOI: 10.1176/ps.48.4.497
|View full text |Cite
|
Sign up to set email alerts
|

An experimental comparison of three types of case management for homeless mentally ill persons

Abstract: Assertive community treatment is superior to broker case management in assisting individuals with serious mental illness who are at risk of homelessness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(27 citation statements)
references
References 6 publications
0
27
0
Order By: Relevance
“…Finally, three trials reported no effect of ACT on income outcomes over usual or supportive services [56,61,62]. No trials measured employment outcomes.…”
Section: Effects Of Assertive Community Treatment (Act)mentioning
confidence: 98%
See 4 more Smart Citations
“…Finally, three trials reported no effect of ACT on income outcomes over usual or supportive services [56,61,62]. No trials measured employment outcomes.…”
Section: Effects Of Assertive Community Treatment (Act)mentioning
confidence: 98%
“…One trial showed that ACT participants with more severe alcohol use disorder experienced faster and earlier improvements in substance use compared to those with less severe alcohol-use disorder or those randomized to usual or supportive services (p<0.01) [25]; however, this difference was not significant by the end of three years. Four trials reported no additional benefits of ACT on substance use outcomes over usual or supportive services [57,59,61,62].…”
Section: Effects Of Assertive Community Treatment (Act)mentioning
confidence: 98%
See 3 more Smart Citations